Peranan Pemerintah Desa dalam Mendukung Pemberdayaan Anak berbasis Rumah Belajar Desa Ononamolo Talafu Kabupaten Nias - Andriyani, Lia; Batubara, Beby Masitho; Lubis, Khairunnisah (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
Village Government is an institution tasked with protecting and regulating communities in certain areas, by Law Number 6 of 2014 concerning villages. One of the important roles of village government is to support the empowerment of children, which is an important aspect in achieving community welfare. This study aims to illustrate the role of village government in empowering children in Ononamolo Talafu Village, Nias Regency. The focus of this research is to understand how the role of village government in supporting learning houses as a basis for empowering children and supporting factors. The theory on which Mintzberg (1989) bases Role theory, which includes interpersonal roles, informational roles, and decision-making roles. With a qualitative approach, this study uses observation, interviews, and documentation as data collection techniques. This study concludes that the active role of village government has a major influence in supporting the empowerment of children through learning houses.